دراسة تحليلية لتغيرات الأرقام القياسية لأسعار المستهلك في سورية خلال الفترة 2011-2016 (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The aim of this research is to study the trend of changes of Consumer Prices Indices in Syria for all types of goods and services, in particular, food commodities, clothing and footwear, housing and fuel. For this purpose, the time series analysis was used for monthly CPI data for the period 2011-2016. The most important results of the study: The average of per capita GDP growth rates was well below the average of annual inflation rates. That has led to a decline in the standard of living of citizens. The ability citizens' spending on goods and commodities has fallen to less than half. In addition, prices of goods and services have increased more than six-fold in general. In detail, food prices have increased eight-fold, prices of clothing and footwear have increased eight-fold, and housing and fuel prices have tripled. هدف هذا البحث إلى دراسة اتجاه تغيرات الأرقام القياسية لأسعار المستهلك في سورية لكافة أنواع السلع والخدمات، وبالتحديد لكل من السلع الغذائية، والألبسة والأحذية، والسكن والوقود. ومن أجل ذلك تم استخدام تحليل السلاسل الزمنية لبيانات شهرية للأرقام القياسية لأسعار المستهلك خلال الفترة 2011-2016. وكانت أهم نتائج الدراسة: إن متوسط معدلات نمو نصيب الفرد من الناتج المحلي الإجمالي أقل بكثير من متوسط معدلات التضخم السنوية، وهو ما أدى إلى انخفاض في مستوى المعيشة للمواطنين. كما أن إمكانية إنفاق المواطن على السلع والخدمات انخفضت إلى أقل من النصف. بالإضافة إلى ذلك فقد زادت أسعار السلع والخدمات أكثر من ستة أضعاف بشكل عام، أما من الناحية التفصيلية فقد زادت أسعار السلع الغذائية ثمانية أضعاف، وأسعار الألبسة والأحذية ثمانية أضعاف، كما زادت أسعار السكن والوقود أكثر من ثلاثة أضعاف.